Kendali Posisi Robot Beroda Dengan Sistem Global Positioning System (GPS) Menggunakan Proportional, Integral dan Derivative (PID) Berbasis Arduino Mega 2560 - Duwi Hariyanto; Eko Setiawan; Dahnial Syauqy (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
A wheeled robot is a technological innovation that makes it easier to mobilize exploration. In carrying out the exploration, the wheeled robot has several obstacles, namely the unstable reading of the robot's position. From this problem, the researcher designed a wheeled robot position control system by adjusting the accuracy of the robot's position. The process of monitoring the position of the robot uses the Ublox Neo-6m GPS module which is controlled by the Arduino Mega2560. Latitude and longitude data obtained from the GPS sensor will be converted into a distance and processed into control. The control used to adjust the position of the robot is PID (Proportional Integral Derivative). For the calculation of PID, this research uses the Zigler-Nichols tuning method in getting to a point. In this study, several tests were carried out for the four controls. The results showed that they had a good response to P and PD controls. Because the two controls achieved set points and had a slight error, where the P control has reached the setpoint in 56.378 seconds with an error = 0.1026 meters with a Kp value of 9.4. Meanwhile, PD control in achieving the target takes 57.384 seconds with an error = 0.1481 meters with a value of Kp = 11.38 and Kd = 11.47.